Functional Impairment in school-aged South African children with ADHD: design, implementation, and evaluation of a targeted intervention - Fischer, Mareli (Department of Psychology, 2025)
Despite the fact that Attention-Deficit/Hyperactivity Disorder (ADHD) is a globally prevalent psychiatric disorder with significant lifelong impact on the quality of life of diagnosed individuals, there is little Africa-based research considering (a) the functional impact of the disorder within the population or (b) locally appropriate interventions that might alleviate that impact. Study 1 was a needs assessment project that described the functional impairment experienced by a South African sample of school-aged children with ADHD (N = 99). The specific focus was on identifying the areas of life where those children faced the most severe challenges related to their symptoms. I used the Mini International Neuropsychiatric Interview for Children (MINI-Kid) as a diagnostic tool, and the Child Behavior Checklist (CBCL), the Strengths and Difficulties Questionnaire (SDQ), and the Impairment Rating Scale (IRS) as measures of functional impairment. Each of these was administered to the parent of a child with ADHD. Results indicated that although ADHD diagnosed children experienced significant impairment in all domains of functioning (including family relationships, social interactions, activities/hobbies, and home life), they experienced especially severe difficulties in the school environment. Study 2, which built on the results from Study 1, described the design, implementation, and testing of a psychosocial intervention (an 8-week parent-training group) targeting the identified domains of ADHD related functional impairment. Participants (parents of school-aged ADHD-diagnosed children) were pseudo-randomly assigned to an intervention group (n = 62), a non-structured support group (n = 66), or a waitlist control group (n = 50). The same diagnostic process and measures of functional impairment as in Study 1 were used to establish the child's pre intervention functioning. The measures were re-administered immediately post-intervention and, for the intervention group only, 6 months later. Results indicated that participants assigned to the intervention condition rated their child's functional impairment as significantly improved following their participation in the 8-week parent-training process, and these improvements were sustained at the 6-month follow-up measurement point. Although analyses detected no significant between-group differences in functional impairment at baseline, at the post-intervention measurement point ratings from intervention group participants were significantly lower than those of participants assigned to the two control groups. The major conclusion, therefore, is that this parent-training intervention is effective in relieving broad-based ADHD-related functional impairment in low-income and low-resource settings. Studying functional impairment and interventions in this way will pave the way for evidence-based, cost-effective treatment plans focused on alleviating the myriad of personal and societal challenges associated with ADHD.